The role of N-glycosylation in B-cell biology and IgG activity. The aspects of autoimmunity and anti-inflammatory therapy - Trzos, Sara; Link-Lenczowski, Paweł; Pocheć, Ewa (Frontiers in Immunology, 2023)
The immune system is strictly regulated by glycosylation through the addition of highly diverse and dynamically changing sugar structures (glycans) to the majority of immune cell receptors. Although knowledge in the field of glycoimmunology is still limited, numerous studies point to the key role of glycosylation in maintaining homeostasis, but also in reflecting its disruption. Changes in oligosaccharide patterns can lead to impairment of both innate and acquired immune responses, with important implications in the pathogenesis of diseases, including autoimmunity. B cells appear to be unique within the immune system, since they exhibit both innate and adaptive immune activity. B cell surface is rich in glycosylated proteins and lectins which recognise glycosylated ligands on other cells. Glycans are important in the development, selection, and maturation of B cells. Changes in sialylation and fucosylation of cell surface proteins affect B cell signal transduction through BCRs, CD22 inhibitory coreceptor and Siglec-G. Plasmocytes, as the final stage of B cell differentiation, produce and secrete immunoglobulins (Igs), of which IgGs are the most abundant N-glycosylated proteins in human serum with the conserved N-glycosylation site at Asn297. N-oligosaccharide composition of the IgG Fc region affects its secretion, structure, half-life and effector functions (ADCC, CDC). IgG N-glycosylation undergoes little change during homeostasis, and may gradually be modified with age and during ongoing inflammatory processes. Hyperactivated B lymphocytes secrete autoreactive antibodies responsible for the development of autoimmunity. The altered profile of IgG N-glycans contributes to disease progression and remission and is sensitive to the application of therapeutic substances and immunosuppressive agents. In this review, we focus on the role of N-glycans in B-cell biology and IgG activity, the rearrangement of IgG oligosaccharides in aging, autoimmunity and immunosuppressive therapy. This is a provisional file, not the final typeset article.